The impact of obesity and hypoxia on left ventricular function and glycolytic metabolism. Issue 4 (23rd April 2014) - Rodriguez, Rosa H.; Bickta, Janelle L.; Murawski, Patrick; O'Donnell, Christopher P.
Abstract We have previously reported that 4 weeks of intermittent hypoxia (IH) exposure, mimicking the hypoxic stress of obstructive sleep apnea, produces compensatory increases in left ventricular (LV) contractility in lean C57BL/6J mice. In this study we compared the effects of 4 weeks IH to 4 weeks of sustained hypoxia (SH) on LV function and cardiac glycolysis in lean C57BL/6J mice and obese ob/ob mice at 10–12 weeks of age. The four exposure conditions were IH (nadir O2 [5–6%] at 60 cycles/h during the 12 h light period), SH (24 h inspired O2 [10%]), and control groups of intermittent air (IA) or room air. Cardiac function was assessed under isoflurane anesthesia (1–2%) by echocardiography and pressure–volume loop analysis and myocardial glycolytic rates were determined ex vivo using radiolabeled 3H‐glucose. Lean mice exposed to IH exhibited increases in contractile parameters which were associated with elevated glycolytic rates (3.4 vs. 5.7 μg/μL·g; P < 0.05). Ob/ob mice did not show any improvements in contractility after IH. Moreover, cardiac glycolytic rates and LV systolic and diastolic function did not differ from IA ob/ob controls. Following SH exposure, lean mice exhibited increased contractility and glycolytic rates (3.8 vs. 5.7 μg/μL·g; P < 0.05), however, LV lumen dimensions were reduced. In contrast, ob/ob mice exposed to SH show compromised systolic and diastolic function associated with unchanging glycolytic rates. These findings demonstrate that, in a murine model of obesity, an inability to increase glycolysis is associated with an absence of an adaptive cardiac response to IH and marked systolic and diastolic dysfunction in response to SH.